Faktor-Faktor Penyebab Terjadinya Obesitas pada Remaja - Juliatin Juliatin; Hasniar Hasniar (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Obesity that occurs in adolescents can occur due to many things, both genetically and also to other external factors. The health problems that result from obesity were varied, and the worse is that it could lead to heart disease which could lead to sudden death. Therefore, it was necessary to have information on what factors were the causes of obesity in children. The purpose of this review article was to determine the factors that cause obesity in children. The method used in this study is the Literature Review method, namely by collecting secondary data from articles or research that has been done previously related to obesity. Search for the required data using the Garuda database, Google Scholar, and Science Direct. The key words used in the literacy search were obesity, youth. The obesity factor AND adolescent AND obesity factors. There were inclusion criteria set in determining the desired literature, namely the object in the research is a teenager, free full text, in Indonesian or English, registered in a scientific journal. Based on the results of the analysis of the literature reviewed, it was found that there are factors that can influence obesity in adolescents, namely: lack of physical activity, often consuming fast food, not having breakfast, lack of knowledge about nutrition, parental income as a supporting factor, and parental genetic factors.